Uczeń, uczennica z FAS/FASD w przestrzeni szkolnej - Buchnat, Marzena; Wojciechowska, Aneta (Studia Edukacyjne, 2025)
Fetal Alcohol Spectrum Disorders (FASD) are a range of developmental and neurological impairments caused by prenatal alcohol exposure. The article outlines the characteristics of FASD and FAS, emphasizing the importance of comprehensive diagnosis and educational support for affected children. It highlights the need for adapting the school environment to reduce sensory hypersensitivity and learning difficulties, thereby promoting better integration of students with FAS/FASD and supporting their educational and social development.